2021
DOI: 10.7150/jca.51551
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potential BRAF Inhibitor Joint Therapy Targets in PTC based on WGCAN and DCGA

Abstract: As the most common mutation in papillary thyroid cancer (PTC), B-type Raf kinase V600E mutation ( BRAF V600E ) has become an important target for the clinical treatment of PTC. However, the clinical application still faces the problem of resistance to BRAF inhibitors (BRAFi). Therefore, exploring BRAF V600E -associated prognostic factors to providing potential joint targets is important for combined targeted therapy with BRAFi. In this study, we com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Backward stepwise Cox regression analysis indicated that SLC34A2 IHC expression as well as age and lymph node status at presentation was independent factors affecting the DFS of PTC cases studied herein. This was in agreement with Han et al [14] whose PTC cases that showed upregulated SLC34A2 gene expression had shorter relapse-free survival. Similarly, SLC34A2 expression has been reported as an independent factor for shorter DFS in CRC and bladder cancer [23].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Backward stepwise Cox regression analysis indicated that SLC34A2 IHC expression as well as age and lymph node status at presentation was independent factors affecting the DFS of PTC cases studied herein. This was in agreement with Han et al [14] whose PTC cases that showed upregulated SLC34A2 gene expression had shorter relapse-free survival. Similarly, SLC34A2 expression has been reported as an independent factor for shorter DFS in CRC and bladder cancer [23].…”
Section: Discussionsupporting
confidence: 92%
“…SLC34A2 is among the genes that have previously been linked to PTCs associated with the BRAF mutation. Previous studies have shown elevated SLC34A2 gene expression in PTC patients associated with BRAF v600E mutations [8,14]. Moreover, another study has even demonstrated that the SLC34A2 gene is downregulated in BRAF wild-type PTCs [15].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Masago et al described the effect of EGFR -activating mutations on PTC development [ 74 ]. Inhibitors of ERRB3, which is also known as a proto-oncogene and a member of the EGFR family, may be effective in the treatment of PTC [ 75 ]. Alternatively, the oncogene KIT , described for its role in PTC and other cancers, encodes a receptor tyrosine kinase that affects cellular growth and differentiation [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result may help improve the clinical outcomes for PTC patients and indicates possibilities for personalized treatment. BRAF mutations are the most frequent mutation subtypes in PTC patients, and targeting BRAF mutants to develop targeted therapy drugs may be an effective method to overcome PTC [ 30 ]. In this study, we comprehensively analyzed the differentially expressed genes in BRAF MT and BRAF WT PTC tissue samples obtained from a TCGA patient cohort.…”
Section: Discussionmentioning
confidence: 99%